Jezik in turizem, Language and Tourism, Sprache und Tourismus - Potočnik Topler, Jasna; Mojca Kompara Lukančič, Mojca (2021)
In the monograph ten scientific chapters oriented towards language for tourism that span from language learning and teaching, to lexicography, minority languages, and selected linguistic concepts are presented. Among them is the analyses of the features of the Slovene LSP Dictionary of Tourism, the question of minority communities and their tourism websites, the collocation strength and contrastive analyses of adjective-noun collocations,  the concept of movement in tertiary education, the analyses of  Slovene –German translations of chosen online menus,  the tourist  web resources as part of the L2 classroom, the connection of linguistic landscapes with tourism,  writing skills in English for Tourism, local language variants of personal names, and teaching and learning language for special purposes during the COVID-19 pandemic.
Keywords: torusim; promotion; LSP; teaching; translation; lexicography